Evaluation of a Hybrid TOEFL Preparation Course Program for Nursing Students Using the CIPP Model - Nashir, Muhammad; Padmadewi, Ni Nyoman; Lokita Purnamika Utami, IGA. (IJORER : International Journal of Recent Educational Research, 2026)
Objective: To enhance nurses' global competitiveness, this study evaluates a hybrid TOEFL preparation program for nursing students at STIKES Banyuwangi. Using the Context, Input, Process, Product (CIPP) model, the evaluation assesses program components to identify effectiveness, relevance, and areas for improvement. Method: This study employed a mixed-methods approach involving 86 nursing students and four academic staff. Data were collected through questionnaires, semi-structured interviews, and documentation and then analysed using descriptive statistics and thematic analysis. Results: The program significantly improved students’ average TOEFL scores, particularly in reading and listening. Context evaluation confirmed the program's relevance and students' appreciation of the hybrid format's flexibility. However, input analysis revealed a lack of nursing-specific content, and process evaluation showed inconsistent online engagement and inadequate feedback. Despite these issues, the program prepared most students to achieve their academic and professional goals. Novelty:This study addresses a crucial research gap by evaluating a hybrid TOEFL preparation program for nursing students. Unlike previous research that focused on English language learners in general and used an offline format, this study offers unique insights into the needs, motivations, and challenges of nursing students in a hybrid model. Furthermore, the comprehensive CIPP model provides a holistic and in-depth evaluation of all program stages. The model explicitly articulates how context evaluation validates program relevance, while Input and Process analyses accurately pinpoint weaknesses, such as a lack of nursing-specific content and inadequate online feedback. Product evaluation quantitatively links these deficiencies to learning outcomes, providing a clear roadmap for targeted, evidence-based program improvement.